2014
DOI: 10.21168/rbrh.v19n4.p137-147
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação de um método de propagação de cheias em rios com aproximação inercial das equações de Saint-Venant

Abstract: Os cálculos de propagação de ondas de cheias em rios são, normalmente, realizados utilizando soluções numéricas das equações de Saint-Venant. No entanto, em modelos hidrológicos de transformação chuva-vazão que representam além do escoamento nos rios, os demais processos do ciclo hidrológico, como a geração de escoamento superficial, a evapotranspiração, e o balanço de água no solo, é comum a utilização de métodos simplificados para representar a propagação de cheias em rios. Entre as técnicas de propagação ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 10 publications
0
20
0
3
Order By: Relevance
“…As in the one-dimensional diffusive model (FAN et al, 2014), the 2-dimensional diffusion model does not include terms of local accelerations, which refer to changes in velocity with respect to time (term i), and terms of convective accelerations, which refer to changes in speed relative to distance (term ii). According to USACE (2016), these terms may be important in dam break studies, especially regarding the stability of the downstream model of the dam.…”
Section: /17mentioning
confidence: 99%
“…As in the one-dimensional diffusive model (FAN et al, 2014), the 2-dimensional diffusion model does not include terms of local accelerations, which refer to changes in velocity with respect to time (term i), and terms of convective accelerations, which refer to changes in speed relative to distance (term ii). According to USACE (2016), these terms may be important in dam break studies, especially regarding the stability of the downstream model of the dam.…”
Section: /17mentioning
confidence: 99%
“…The hydraulic radius is approximated by the depth ( R h ≈ ), considering that the rivers cross sections have a width much larger than the depth. The derivatives of the dynamic equation are approximated by a numerical scheme of progressive finite differences in space and time, which results in Equation 4, as presented in Fan et al (2014).…”
Section: One-dimensional Inertial Modelmentioning
confidence: 99%
“…Montero et al (2013) demonstrated that the inertial model has advantages over the diffusion wave model when compared to complete solutions of the Saint-Venant equation. Fan et al (2014) tested the inertial formulation for representing one-dimensional flow in rivers. The authors showed their applicability in scenarios with high and low rivers' slope and subjected to downstream effects, such as backwater and tide.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations